The Effect Of Trust And Commitment On Customer Loyalty Of Bprs Botani Bina Rahmah With Customer Satisfaction As a Mediation Variable - Ayi Hilman Faizin; Yuniningsih; Muhadjir Anwar (Economics and Business Journal (ECBIS), 2026)
This research is motivated by the importance of building and maintaining customer loyalty at the Botani Bina Rahmah Sharia Rural Financing Bank (BPRS), a financial institution that plays a strategic role in strengthening the sharia-based economy and promoting financial inclusion at the micro level. The phenomenon of increasing account openings without a corresponding increase in customer retention indicates challenges in managing long-term relationships with customers. Trust and commitment are believed to be important factors in creating loyalty, but the effectiveness of both is often influenced by the level of customer satisfaction. Therefore, this study was conducted to analyze satisfaction as a mediating variable in the relationship between trust and commitment and customer loyalty. This study aims to analyze: (1) the effect of trust on customer loyalty, (2) the effect of commitment on customer loyalty, (3) the effect of trust on loyalty through customer satisfaction as a mediating variable, and (4) the effect of commitment on loyalty through customer satisfaction as a mediating variable. The research approach used is quantitative with a cross-sectional design. Data were collected by distributing Likert-scale questionnaires to 100 active customer respondents of BPRS Botani Bina Rahmah. Data analysis was carried out using Structural Equation Modeling–Partial Least Squares (SEM–PLS) with the help of SmartPLS software to test the validity and reliability of constructs and the relationships between variables in the structural model. The results of the study indicate that trust has a positive and significant effect on customer loyalty, while commitment does not have a significant direct effect on loyalty. Customer satisfaction is proven to act as a significant mediating variable in the relationship between trust and loyalty, as well as between commitment and loyalty. These findings confirm that BPRS customer loyalty is more influenced by the level of trust and satisfaction built through service quality and conformity to Sharia values. Practically, BPRS management needs to strengthen contract transparency, improve service consistency, and optimize digital channels to strengthen trust, increase satisfaction, and ultimately encourage sustainable customer loyalty.